INOVASI PENDIDIKAN DENGAN MEMANFAATKAN TEKNOLOGI DIGITAL DALAM UPAYA MENYONSONG ERA REVOLUSI INDUSTRI 4.0 - Emalia Emalia; Farida Farida (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Educational innovation is a new change, and qualitatively different from the things that exist before, and deliberately sought to improve the ability to achieve certain goals in education. The purpose of this study is to describe the form of innovation carried out in the world of education by utilizing technology, especially in the era of industrial revolution 4.0. The research method used is a qualitative method. The results of the research conducted show that there are many models in the implementation of educational innovations including conception of change, proposals for change, adoption and implementation. The stages in the process of educational innovation begin with the initiation of change, there is an agenda (setting), matching (matching), re-definition or re-structuring, clarification and routine. The forms of innovation that have been carried out in education in Indonesia have started with pioneering development school projects, 1975 curriculum, civil service projects, open junior high schools, open universities, renewal of education education systems, 1984 curriculum, 1994 curriculum, KBK curriculum, KTSP curriculum, 2013 curriculum. Currently with the development of information technology and the echoing of the industrial revolution era 4.0, educational innovation also needs to be done. The form of innovation carried out in the context of optimizing education to meet the industrial revolution era is the establishment of digital learning as it is now known as the In-Network Learning System (SPADA)